PERTANGGUNGJAWABAN DEBITOR ATAS UTANG BARU YANG TIMBUL DARI GAGALNYA GOING CONCERN TANPA IZIN HAKIM PENGAWAS - Vinsensius Jala; Putu Eka Trisna Dewi; Benyamin Tungga (Faculty of Law, Mahasaraswati University, Denpasar, 2025)
This research aims to analyze the problem of debtor responsibility for new debts arising from the failure of a going concern without the permission of the supervising judge. The method used to obtain answers to these research problems is normative juridical research using a statutory approach, case approach and conceptual approach, then answering research problems is based on primary legal materials and secondary legal materials collected using library study techniques. In this research, the results obtained show that bankrupt debtors who carry out going concern actions do not comply with the provisions regulated in the Bankruptcy Law, namely without permission from the supervising judge, this is an unlawful act which can be held accountable based on the principle of responsibility based on liability based on fault as regulated in Article 1365 Civil Code. In this way, the bankrupt debtor who is going concern without the permission of the supervisory judge is responsible for paying off all new debts that arise after going concern illegally.